2002
DOI: 10.1002/jcb.10188
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing during chondrogenesis: Modulation of fibronectin exon EIIIA splicing by SR proteins

Abstract: The alternative exon EIIIA of the fibronectin gene is included in mRNAs produced in undifferentiated mesenchymal cells but excluded from differentiated chondrocytes. As members of the SR protein family of splicing factors have been demonstrated to be involved in the alternative splicing of other mRNAs, the role of SR proteins in chondrogenesis-associated EIIIA splicing was investigated. SR proteins interacted with chick exon EIIIA sequences that are required for exon inclusion in a gel mobility shift assay. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
(60 reference statements)
4
18
0
Order By: Relevance
“…Thus, higher amounts or activities of certain splice-regulating proteins may lead to a differential pattern of splicing in this individual and therefore to partial phenotype rescue. Recent studies revealed that the modulation of exon splicing by SR proteins depends on the cellular context [Kuo et al, 2002]. As we examined mRNA in lymphoblastoid cells, conclusions concerning different splice patterns in other tissues are not warranted, especially those that may have a higher impact on pathogenesis.…”
Section: Mrna Variations Of Thetrim37 Genementioning
confidence: 95%
“…Thus, higher amounts or activities of certain splice-regulating proteins may lead to a differential pattern of splicing in this individual and therefore to partial phenotype rescue. Recent studies revealed that the modulation of exon splicing by SR proteins depends on the cellular context [Kuo et al, 2002]. As we examined mRNA in lymphoblastoid cells, conclusions concerning different splice patterns in other tissues are not warranted, especially those that may have a higher impact on pathogenesis.…”
Section: Mrna Variations Of Thetrim37 Genementioning
confidence: 95%
“…SR proteins are well-established regulators of the exon inclusion/exclusion of alternative splicing mechanisms (21)(22)(23)(24). Based on previous findings from our laboratory demonstrating that PP1 activation by de novo ceramide generation can regulate both the phosphorylation status of SR protein and the pre-mRNA processing of caspase-9 (15, 20), we hypothesized that an SR protein isoform is involved in the regulation of the alternative splicing mechanism of caspase-9 pre-mRNA.…”
Section: Srp30a Regulates the Alternative Splicing Of Caspase-9mentioning
confidence: 98%
“…In fact, in many experimental systems, single nucleotide substitutions have been known to affect ESE elements (11,13,14,44). This may be particularly relevant for the EDA exon, as proteins belonging to the SR protein family have a well-known ability to alter EDA inclusion in the mature mRNA (19,40,42). The use of SR scoring matrices to identify potential SR binding sites has been very useful in functionally characterizing several diseasecausing mutations in the BRCA1 and SMN1 genes, as recently reviewed (13).…”
Section: Comparison Of Alternative Splicing Regulation In the Mouse Amentioning
confidence: 99%